2009
DOI: 10.1002/jssc.200800464
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of striatal neuronal cell cultures after morphine administration

Abstract: Using primary neuronal cell culture assays, combined with 2-D gel electrophoresis and capillary LC-MS, we identified differences in proteomes between control and morphine-treated cells. Statistically significant differences were observed among 26 proteins. Nineteen of them were up-regulated, while seven were down-regulated in morphine-treated cell populations. The identified proteins belong to classes involved in energy metabolism, associated with oxidative stress, linked with protein biosynthesis, cytoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…In an earlier review, we presented a detailed summary of proteins involved in these biological processes and discussed their potential roles in the physiological conditions of drug dependence [17]. The correlation of these biological processes with each addictive drug also has been discussed in some proteomics studies [11,28,34,43,46,52].…”
Section: Proteins Associated With the Exposure Of Multiple Addictive mentioning
confidence: 97%
See 1 more Smart Citation
“…In an earlier review, we presented a detailed summary of proteins involved in these biological processes and discussed their potential roles in the physiological conditions of drug dependence [17]. The correlation of these biological processes with each addictive drug also has been discussed in some proteomics studies [11,28,34,43,46,52].…”
Section: Proteins Associated With the Exposure Of Multiple Addictive mentioning
confidence: 97%
“…Most of the published investigations are based on animal models or cell lines. Because of their importance in the development and maintenance of drug dependence, a few brain regions, such as the NAc [50], frontal cortex [12,51], hippocampus [12], and striatum [12,52], are the primary targets of proteomics analysis in the study of morphine, heroin, or butorphanol addiction. Whole brain [53] or components of the nervous system, such as the spinal cord [54], dorsal root ganglia [55], or cultured neuronal cells [56,57], also have been investigated.…”
Section: Morphine/heroin/butorphanolmentioning
confidence: 99%
“…2D-PAGE was performed following Bodzon-Kulakowska [32], but with some modifications. The first dimension was performed on 18 cm immobilized non-linear gradient strips at pH 5-8.…”
Section: D-pagementioning
confidence: 99%
“…Briefly, peptides were loaded onto a reversed phase trapping column (0.3 mm ϫ 5.0 mm), and subsequently resolved on a capillary C 18 PepMap column (0.1 mm ϫ 150 mm, 3 m, 100 Å, Dionex). Peptides were eluted using a 70 min gradient of solvent A and solvent B as follows: 5% to 8% B from 0 -4 min, 18% B at 34 min, 35% B at 57 min, and 95% B at 64 min.…”
Section: Methodsmentioning
confidence: 99%
“…Proteomic analysis has been used to elucidate both the in vitro (18,19) and in vivo (20 -26) changes in the protein profiles of synapses that exhibit drug-induced alterations in response to opiate exposure. For example, the use of subcellular fractionation, which allows for the separation and generation of protein fractions selectively enriched in either pre-or postsynaptic proteins (25,27), in combination with proteomic analysis has revealed that an acute escalating dose of morphine administration produces significant alterations in the postsynaptic density (PSD) 1 associated protein network in the hippocampus.…”
mentioning
confidence: 99%